Occult hepatitis C virus infection in volunteer blood donors in Shaanxi province - Yan GUO; Chen HE; Xiaohua ZHAO; Yong DUAN; Hua XU; Wen WANG; Guoquan ZHANG; Jin LI (Zhongguo shuxue zazhi, 2022)
Objective To investigate the prevalence of occult hepatitis C virus infection (OCI) in Shaanxi blood donors and characterize the occult hepatitis C virus in this cohort. Methods Between July and September of 2019, 112, 117, 46, and 75 blood samples were obtained from eligible donors, alanine aminotransferase (ALT) elevated donors(ALT>50 U/L), hepatitis B virus surface antigen (HBsAg) positive donors, and anti-hepatitis C virus (anti-HCV) positive donors, respectively. Peripheral blood lymphocytes (PBMCs) were isolated from all the samples. HCV 5′UTR was amplified from total RNA of PBMCs using reverse transcription nested PCR (RT-Nested PCR) to detect the infection status of OCI in blood donors. HCV RNA core/E2 region was amplified from HCV RNA positive samples with RT-Nested PCR to determine HCV genotypes and subtypes via sequencing. Results Two (2.67%, 2/75) cases of OCI were identified in anti-HCV positive samples, 1(0.85%, 1/117) case of OCI was identified in abnormal ALT samples, and all OCI were genotyped as 1b. OCI was not found in HBsAg positive and eligible blood donors. Conclusions Our findings suggest that OCI does exist among Shaanxi blood donors and that ALT may be useful in diagnosing OCI.